Two new species of Crinipellis (Marasmiaceae, Agaricales) from Kerala State, India - Sharafudheen, Shahina A.; Manimohan, Patinjareveettil; Latha, K. P. Deepna (Phytotaxa, 2023)
Two new species of Crinipellis, Crinipellis minima and C. fibrillosa, are described from Kerala State, India, based on both morphological characteristics and molecular phylogenetic analysis using the internal transcribed spacers of nuclear ribosomal DNA (nrITS). Detailed descriptions, photographs and comparisons with phenetically and phylogenetically related species are provided. The nrITS-based phylogenetic tree inferred from the Maximum Likelihood analysis confirmed both the novelty and the placement of these species within the genus Crinipellis.